2021
DOI: 10.3389/fgene.2021.638558
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Integrin-Linked Kinase in Colorectal Cancer Growth and Progression via Regulating Senescence and Immunity

Abstract: Integrin-linked kinase (ILK) has been implicated as a molecular driver and mediator in both inflammation and tumorigenesis of the colon. ILK functions as an adaptor and mediator protein linking the extracellular matrix with downstream signaling pathways. ILK is broadly expressed in many human tissues and cells. It is also overexpressed in many cancers, including colorectal cancer (CRC). Inflammation, as evidenced by inflammatory bowel disease (IBD), is one of the highest risk factors for initiating CRC. This h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 193 publications
0
18
0
Order By: Relevance
“…Integrin-linked kinase (ILK) plays a key role as a multifunctional effector of growth factor signaling and cell–matrix interaction [ 58 ]. Some studies have found that ILK is associated with the process of EMT and immune, which could be seen as an EMT-immune-related gene [ 59 , 60 ]. A study found that ILK is up-regulated in colorectal cancer and other tumors [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin-linked kinase (ILK) plays a key role as a multifunctional effector of growth factor signaling and cell–matrix interaction [ 58 ]. Some studies have found that ILK is associated with the process of EMT and immune, which could be seen as an EMT-immune-related gene [ 59 , 60 ]. A study found that ILK is up-regulated in colorectal cancer and other tumors [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that ILK is associated with the process of EMT and immune, which could be seen as an EMT-immune-related gene [ 59 , 60 ]. A study found that ILK is up-regulated in colorectal cancer and other tumors [ 60 ]. We found that ILK is down-regulated in colon cancer and leads to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that myeloid-ILK deficiency reduced inflammation of experimental colitis by regulating neutrophil infiltration and cytokine production ( 32 ). While this suggested that ILK plays an important role in the inflammatory tumor microenvironment in colon cancer ( 36 ), mechanisms involved remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have previously shown that myeloid-ILK deficiency reduced intestinal inflammation in experimental colitis by regulating neutrophil infiltration and cytokine production ( 32 ). These studies suggest that while ILK is an essential molecule for promoting the inflammatory tumor microenvironment ( 36 ) and its different compartments, its importance in regulating the different TME components remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Integrin-linked kinase (ILK) is conceptually a serine-threonine protein kinase and can control many biological behaviors of cells, including growth, survival, differentiation and migration [8]. Many studies show that ILK overexpression is associated with the carcinogenesis and metastasis of diverse cancers, such as hepatocellular carcinoma, colorectal cancer and BC [9][10][11].…”
Section: Agingmentioning
confidence: 99%